KEBENARAN SEMU: REFLEKSI POST-TRUTH DI DUNIA HIPERREALITAS (ANALISIS SEMIOTIKA ROLAND BARTHES PADA FILM “FYRE FRAUD”) (Jurnal Washiyah: Jurnal Kajian Dakwah dah Komunikasi, 2022)
This study aims to determine post-truth representation in the context of virtual world hyperreality, based on the 2017 Fyre Festival case study documented in the film “Fyre Fraud”. Postmodern humans live in a post-truth digital era; relating to a situation where emotions influence public opinion more than objective facts. Post-truth is increasingly spreading due to the rise of simulacra machines, known as cyberspace. The study takes a descriptive qualitative method and employs Roland Barthes' semiotic analysis model in its media text analysis research. The results reveal that the "Fyre Fraud" documentary represents post-truth, symbolized through audiovisual and cinematographic techniques. Representation is found in six scenes: (1) Manipulating emotions and personal beliefs, shown through the FOMO cyberculture movement. (2) Human behavior spending time looking for information in cyberspace indicates a well-informed millennial society. (3) The influencers and social media's presence as a catalyst for agenda setting. (4) Visualization of information chaos in the form of misinformation and disinformation through Fyre Festival promotional materials. (5) Truth alteration through photo manipulation to produce an alternate reality. (6) Truth is repressed and ignored through news wars and comment deletion.